Undang undang perkawinan. UU No. 1 Th.1974, PP No. 9 Th.1975, PP No. 10 Th.1983, PP No. 45 Th.1990 - [Tidak Terdaftar] (PUSTAKA TINTA MAS, 1990)
Undang undang perkawinan. UU No. 1 Th.1974, PP No. 9 Th.1975, PP No.10 Th.198